Ubiquitination for destruction or survival? - Garimella Lakshmi et al. (Journal of Plant Biology, 2011)
The ubiqquitin proteasome pathway and its role in plant developement, maintenance and survival have gained a lot of importanc in the recent times. The fact that the Ubiquitin Proteasome Systems(UPS) is very complex and influences every aspect of plant life makes it a topic of current research. With the discovery of this pathway, it is now well esablished that the protien composition in a cell is maintained, not only by transcription and translation but also by ubiquitin-mediated proteolysis. While polyubiquitination serves as a signal for proteolysis by 26s proteasome, monoubiquitination modulates the activity of the protien. This review focuses on the brief history of the discovery of UPS, persent knowledge about its mechanism and regulation, about its huge diversity, contribution in normal cell functioning and role in plant developement and survival.
Keywords: 26s proteasome; Culling ring ligases; E3 ligase; RING finger; Ubiquitin; Ubiquitin activating enzyme; Ubiquitin conjugating enzyme; Ubiquitin proteasome system